Additive manufacturing in the apparel supply chain — impact on supply chain governance and social sustainability. Issue 7 (28th June 2021) - Hohn, Marlene M.; Durach, Christian F.
Abstract : Purpose: Focusing on the apparel industry, this study extends current knowledge on how additive manufacturing (AM) may impact global supply chains regarding structures of interorganizational governance and the industry's social-sustainability issues. Design/methodology/approach: Following an exploratory research design, two consecutive Delphi studies, with three survey rounds each, were conducted to carve out future industry scenarios and assess AM's impact on supply chain governance and social sustainability. Findings: The implementation of AM is posited to reinforce existing supply chain governance structures that are dominated by powerful apparel retailers. Retailers are expected to use the increased production speed and heightened market competition to enforce faster fashion cycles and lower purchasing prices, providing a grim outlook for future working conditions at the production stage. Social implications: Against the common narrative that technological progress increases societal well-being, this study finds that new digital technologies may, in fact, amplify rather than improve existing social-sustainability issues in contemporary production systems. Originality/value: This article contributes to the nascent research field of AM's supply chain impact as one of the first empirical studies to analyze how AM introduction may impact on interorganizational governance while specifically addressing potential social-sustainability implications. The developed propositions relate to and extend the resource dependence and stakeholder perspectives on governance and social sustainability in supply chains. For managers, our results enrich the discussion about the potential use of AM beyond operational viability to include considerations on the wider implications for supply chains and the prevailing working conditions within them.